Mushroom House Enterprise - Johari, Siti Noor Aziela; Norhaidie, Nurulain; Muhajirin, Rinah; Putling, Erra Faerra; Darwis, Nuraidah (2013)
Our company name is Mushroom House Enterprise. The business of our company has been decided on the form of partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to plant and supply Cendawan Tiram kelabu. All partners are encourage and entitled to participate in all business management. We have agreed that Siti Noor Aziela binti Johari as the General Manager. The Marketing Manager is Rinah binti Muhajirin and Erra Fazerra binti Putling as the Operational Manager. Nurulain binti Norhaidie as the Administration Manager and Nuraidah binti Darwis as our Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the criteria of experience, skills and abilities. The management team will be lead by the General Manager and the other managers will help in other process. The task and responsibilities of a General Manager is responsible in the process of controlling, leading, organizing as well as plan the entire business. The marketing manager will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. Meanwhile, the Operation Manager is responsible to the operation of the business as whole. The Operation Manager will supervise, coordinate and make sure the operation of the business is running smoothly. The Administrative Manager will responsible in doing for all jobs relating to office administration business. This includes the process of selecting the staff, hiring staff, remuneration schedule of salary and wages and also planning the fringe benefits for the staff. Lastly, the Financial Manager will be accountable to handle the financial matters such as preparing the budget, financial statement for expenses, controlling the flow of the money of the organization and also preparing account statement at the end of the accounting period for auditing purposes.